Synthesis, Characterization and Studying the Enzyme Activity of New Benzothiazole Schiff Base Ligand (HL) and Its Complexes with Some of Metal Ions - Al-Zaidi, Basim H.; Abed, Asia H.; Hafedh, Fadhel R.; Niseaf, Ali N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new heterocyclic Schiff bases ligand (HL) derived from condensation of 2-Amino-4-methylbenzothiazole with 4-Diethylaminosalicylaldehyde have been synthesized and characterized by (FTIR & UV.Vis) spectroscopies, (1H & 13C)NMR spectra, mass spectrum, elemental microanalysis (C,H,N,S). Metal complexes with Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) ions have been also synthesized and characterized by (FTIR & UV.Vis) spectroscopies, flame atomic absorption, molar conductivity measurements and magnetic susceptibility. These studies indicate that the mole ratio (L:M) is (2:1) for Co(II) complex and (1:1) for other complexes. The spectral results indicate that the ligand coordinates with metal ions as monobasic bidentate, via azomethine nitrogen and phenolic oxygen atoms. The study suggested octahedral geometry for Co(II), Ni(II) and Zn(II) complexes and square planar and tetrahedral geometries for Cu(II) and Cd(II) complexes, respectively. The enzyme activity of the ligand and its metal complexes with acetylcholine esterase1 (AChE) have also been studied. The study of enzyme activity indicates that the ligand and its metal complexes revealed different inhibition behaviors.